BIMBINGAN KONSELING PRA NIKAH SEBAGAI UPAYA MEWUJUDKAN KELUARGA BAHAGIA DAN IDEAL DALAM PERSPEKTIF HUMANISTIK CARL R. ROGERS - Rahmat Hidayat; Sugianto Sugianto; Esen Pramudya Utama; Mohd Asrul Bin Mohd Noor (Jurnal Bimbingan Penyuluhan Islam, 2022)
Marriage is sunnatullah, for everything in the world is created in pairs. In this paper, the author aims to uncover the guidance of premarital counseling to realize a happy family perspective of Carl R. Rogers. The results showed that the premarital counseling guidance approach was from the perspective of Carl R. Roger through a humanistic approach. This approach is carried out with the stages of forming a mindset and forming a soul pattern based on Islamic religious values. thus, if the mindset and pattern of the soul are based on Islamic values, then the justification of the motivation will be in accordance with the rules of Islamic shari'a.